HEAD UP 30˚ IN HEAD INJURY PATIENTS (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2023)
The increase in intracranial pressure due to head injury can lead to compression in the brain area, resulting in the emergence of pain. Maintaining a head position at a 30˚ angle or higher can alleviate headache by enhancing oxygen supply to the brain. This study aims to illustrate the use of a head-up position at 30˚ in head injury patients as an effort to reduce pain. The research employed the Pre-Experimental Design method with the One Group Pre Test-Post Test Design approach, involving 30 participants as samples at the Putri Hijau Medan Hospital, conducted from March to April 2023. Sample selection was purposive, utilizing an observation sheet as a measuring tool, and the collected data were processed using SPSS 16.0. Dataanalysis was carried out using the Wilcoxon test with a significance level (α) of 0.05. The research results revealed a p-value of 0.00, indicating that the administration of a head-up position at 30o is effective in reducing pain in head injury patients. Recommendations are provided to nurses to implement this 30˚ head-up position as a measure to alleviate pain in head injury patients.Keywords: Head up 30˚, Intracranial, Pain Scale
Keywords: Head up 30˚; Intrakranial; Skala Nyeri